TWO TEXTUAL NOTES ON CICERO, DE OFFICIIS. (December 2019) - Dyck, Andrew R.
Abstract : (1) 1.21: ex quo, quia suum cuiusque fit eorum quae natura fuerant communia quod cuique obtigit, id quisque teneat; †e quo si quis† sibi appetet, uiolabit ius humanae societatis. The base text cited is that of Winterbottom. After discussing the origin of private property, Cicero asserts that it should be maintained as distributed ( id quisque teneat ). Of the matter marked corrupt, e quo (sometimes written ex quo or with a letter deleted after e ; see Winterbottom's apparatus criticus) is likely to be a repetition of the preceding ex quo and therefore intrusive (as Winterbottom suggested ad loc.: 'fort. delendum'). si quis evidently requires supplementation. Müller (after marginal corrections in printings of Lambinus's edition) inserted quid after quis, but in that case one would expect a further specification ( quid alienum or the like). The better candidate for the supplement after quis is perhaps plus, the reading of the two fifteenth-century Munich codices 7020 and 650 (M and S respectively), an easy error. Cf. Cic. Leg. agr. 3.13: cum plus appetat quam ipse Sulla …; Sull. 84: ut ego mihi plus appetere coner quam quantum omnes inimici inuidique patiantur.